The great inflation of the 1970s - Fabrice Collard; Harris Dellas (European Central Bank (ECB), 2004)
Was the high inflation of the 1970s mostly due to incomplete information about the structure of the economy (an unavoidable mistake as suggested by Orphanides, 2000)? Or, to weak reaction to expected inflation and/or excessive policy activism that led to indeterminacies (a policy mistake, a scenario suggested by Clarida, Gali and Gertler, 2000)? We study this question within the NNS model with policy commitment and imperfect information, requiring that the model have satisfactory overall empirical performance. We find that both explanations do a good job in accounting for the great inflation. Even with the commonly used specification of the interest policy rule, high and persistent inflation can occur following a significant productivity slowdown if policymakers significantly and persistently underestimate ”core” inflation.
Keywords: E32; E52; 330; imperfect information; indeterminacy; inflation; Kalman filter; policy rule